The Effect of Preeclampsia Prevention Videos on Knowledge, Attitudes and Self-Efficacy of Pregnant Women in Semarang City, Indonesia - Anjelika, Ratna; Widjanarko, Bagoes; Sriatmi, Ayun (Universitas Airlangga, 2025)
Background: Preeclampsia is one of the leading causes of maternal mortality in the world, so efforts are needed to prevent preeclampsia. Prevention efforts can be carried out through health education with videos, given the development of information technology that makes it easier to deliver health information. Objective: This study aims to determine the effect of education and the magnitude of changes in values using videos about preeclampsia on knowledge, attitudes and self-efficacy of pregnant women. Methods: This study is a quantitative study with a quasi-experimental design with a pretest posttest with control group design. The research sample was 30 pregnant women in the intervention group and 30 people in the control group. Conclusion: Statistical tests using Wilcoxon in the intervention group showed an increase in the value of knowledge, attitudes and self-efficacy after getting the intervention with a p-value of 0,000 or < 0,05. Statistical tests using Mann Whitney found that there was no initial difference in knowledge, attitudes and self-efficacy of pregnant women in the intervention group and control group, but after getting the intervention in both groups it was known that there were differences in knowledge, attitudes and self-efficacy after getting the intervention with a p-value of 0,000 or < 0,05. And statistical tests using the Linear Mixed Model found that there was an increase in knowledge scores by 15,93%, attitudes by 5,82% and self-efficacy of pregnant women by 6,35% due to the intervention. Conclusion: There is an effect of providing education using video media and leaflets on knowledge, attitudes and self-efficacy in pregnant women compared to only using leaflets, there are differences in the scores of knowledge, attitudes and self-efficacy of pregnant women in the intervention group and control group after receiving education using video, and there is an increase in knowledge scores, attitudes and self-efficacy after receiving the intervention.